Answer:
No, I do not agree with the conjecture because 1 is not a prime number.
Step-by-step explanation:
A prime number is one that can be divided by 1 and itself only. Thus it can be expressed in 2 factors only, 1 and the number itself.
Examples are; 2, 3, 5, 13, 19 , 23 etc.
So, 2 = 1 x 2
3 = 1 x 3
23 = 1 x 23
Prime numbers must be expressed as the product of 1 and the number.
The conjecture that every prime number can be expressed as the product of two prime numbers is false. Because 1 is not a prime number, since it has no 2 factors.
<h2>
Answer</h2>
After the dilation
around the center of dilation (2, -2), our triangle will have coordinates:
![R'=(2,3)](https://tex.z-dn.net/?f=R%27%3D%282%2C3%29)
![S'=(2,-2)](https://tex.z-dn.net/?f=S%27%3D%282%2C-2%29)
![T'=(-3,-2)](https://tex.z-dn.net/?f=T%27%3D%28-3%2C-2%29)
<h2>Explanation</h2>
First, we are going to translate the center of dilation to the origin. Since the center of dilation is (2, -2) we need to move two units to the left (-2) and two units up (2) to get to the origin. Therefore, our first partial rule will be:
→![(x-2, y+2)](https://tex.z-dn.net/?f=%28x-2%2C%20y%2B2%29)
Next, we are going to perform our dilation, so we are going to multiply our resulting point by the dilation factor
. Therefore our second partial rule will be:
→![\frac{5}{3} (x-2,y+2)](https://tex.z-dn.net/?f=%5Cfrac%7B5%7D%7B3%7D%20%28x-2%2Cy%2B2%29)
→![(\frac{5}{3} x-\frac{10}{3} ,\frac{5}{3} y+\frac{10}{3} )](https://tex.z-dn.net/?f=%28%5Cfrac%7B5%7D%7B3%7D%20x-%5Cfrac%7B10%7D%7B3%7D%20%2C%5Cfrac%7B5%7D%7B3%7D%20y%2B%5Cfrac%7B10%7D%7B3%7D%20%29)
Now, the only thing left to create our actual rule is going back from the origin to the original center of dilation, so we need to move two units to the right (2) and two units down (-2)
→![(\frac{5}{3} x-\frac{10}{3}+2,\frac{5}{3} y+\frac{10}{3}-2)](https://tex.z-dn.net/?f=%28%5Cfrac%7B5%7D%7B3%7D%20x-%5Cfrac%7B10%7D%7B3%7D%2B2%2C%5Cfrac%7B5%7D%7B3%7D%20y%2B%5Cfrac%7B10%7D%7B3%7D-2%29)
→![(\frac{5}{3} x-\frac{4}{3} ,\frac{5}{3}y+ \frac{4}{3})](https://tex.z-dn.net/?f=%28%5Cfrac%7B5%7D%7B3%7D%20x-%5Cfrac%7B4%7D%7B3%7D%20%2C%5Cfrac%7B5%7D%7B3%7Dy%2B%20%5Cfrac%7B4%7D%7B3%7D%29)
Now that we have our rule, we just need to apply it to each point of our triangle to perform the required dilation:
![R=(2,1)](https://tex.z-dn.net/?f=R%3D%282%2C1%29)
![R'=(\frac{5}{3} x-\frac{4}{3} ,\frac{5}{3}y+ \frac{4}{3})](https://tex.z-dn.net/?f=R%27%3D%28%5Cfrac%7B5%7D%7B3%7D%20x-%5Cfrac%7B4%7D%7B3%7D%20%2C%5Cfrac%7B5%7D%7B3%7Dy%2B%20%5Cfrac%7B4%7D%7B3%7D%29)
![R'=(\frac{5}{3} (2)-\frac{4}{3} ,\frac{5}{3}(1)+ \frac{4}{3})](https://tex.z-dn.net/?f=R%27%3D%28%5Cfrac%7B5%7D%7B3%7D%20%282%29-%5Cfrac%7B4%7D%7B3%7D%20%2C%5Cfrac%7B5%7D%7B3%7D%281%29%2B%20%5Cfrac%7B4%7D%7B3%7D%29)
![R'=(\frac{10}{3} -\frac{4}{3} ,\frac{5}{3}+ \frac{4}{3})](https://tex.z-dn.net/?f=R%27%3D%28%5Cfrac%7B10%7D%7B3%7D%20-%5Cfrac%7B4%7D%7B3%7D%20%2C%5Cfrac%7B5%7D%7B3%7D%2B%20%5Cfrac%7B4%7D%7B3%7D%29)
![R'=(2,3)](https://tex.z-dn.net/?f=R%27%3D%282%2C3%29)
![S=(2,-2)](https://tex.z-dn.net/?f=S%3D%282%2C-2%29)
![S'=(\frac{5}{3} (2)-\frac{4}{3} ,\frac{5}{3}(-2)+ \frac{4}{3})](https://tex.z-dn.net/?f=S%27%3D%28%5Cfrac%7B5%7D%7B3%7D%20%282%29-%5Cfrac%7B4%7D%7B3%7D%20%2C%5Cfrac%7B5%7D%7B3%7D%28-2%29%2B%20%5Cfrac%7B4%7D%7B3%7D%29)
![S'=(\frac{10}{3} -\frac{4}{3} ,-\frac{10}{3}+ \frac{4}{3})](https://tex.z-dn.net/?f=S%27%3D%28%5Cfrac%7B10%7D%7B3%7D%20-%5Cfrac%7B4%7D%7B3%7D%20%2C-%5Cfrac%7B10%7D%7B3%7D%2B%20%5Cfrac%7B4%7D%7B3%7D%29)
![S'=(2,-2)](https://tex.z-dn.net/?f=S%27%3D%282%2C-2%29)
![T=(-1,-2)](https://tex.z-dn.net/?f=T%3D%28-1%2C-2%29)
![T'=(\frac{5}{3} (-1)-\frac{4}{3} ,\frac{5}{3}(-2)+ \frac{4}{3})](https://tex.z-dn.net/?f=T%27%3D%28%5Cfrac%7B5%7D%7B3%7D%20%28-1%29-%5Cfrac%7B4%7D%7B3%7D%20%2C%5Cfrac%7B5%7D%7B3%7D%28-2%29%2B%20%5Cfrac%7B4%7D%7B3%7D%29)
![T'=(-\frac{5}{3} -\frac{4}{3} ,-\frac{10}{3}+ \frac{4}{3})](https://tex.z-dn.net/?f=T%27%3D%28-%5Cfrac%7B5%7D%7B3%7D%20-%5Cfrac%7B4%7D%7B3%7D%20%2C-%5Cfrac%7B10%7D%7B3%7D%2B%20%5Cfrac%7B4%7D%7B3%7D%29)
![T'=(-3,-2)](https://tex.z-dn.net/?f=T%27%3D%28-3%2C-2%29)
Now we can finally draw our triangle:
The last one is that correct answer.
2x^2 +7x -4
All you have to do is go to the location of the number and go over the other location of the other number